2018
DOI: 10.1111/bjd.16602
|View full text |Cite
|
Sign up to set email alerts
|

Our judgement is influenced by conflict of interest

Abstract: Linked Article: Kayapa et al. Br J Dermatol 2018; 178:1464–1465.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Although exposure to industry can begin as early as the medical school years, dermatology residency represents a significant period of time during which residents are the target recipients of certain sponsored educational activities or materials. A few articles have been written about CoI in dermatology as well as the types of interaction between dermatologists and industry (Anstey, 2018, Ashack et al, 2015, Feng et al, 2016), but there is a dearth of literature on the impact of industry relationships as it pertains to dermatology education. In one study, resident physicians from hospitals associated with Mount Sinai School of Medicine showed that most respondents found industry funding of education and industry-supported educational materials useful, despite finding bias in lectures (Korenstein et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although exposure to industry can begin as early as the medical school years, dermatology residency represents a significant period of time during which residents are the target recipients of certain sponsored educational activities or materials. A few articles have been written about CoI in dermatology as well as the types of interaction between dermatologists and industry (Anstey, 2018, Ashack et al, 2015, Feng et al, 2016), but there is a dearth of literature on the impact of industry relationships as it pertains to dermatology education. In one study, resident physicians from hospitals associated with Mount Sinai School of Medicine showed that most respondents found industry funding of education and industry-supported educational materials useful, despite finding bias in lectures (Korenstein et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As not all journals required these disclosures, closer inspection of the funding source, the author’s profiles and affiliations was conducted. In view of even subtle commercial influences in dermatology being (a) common (Batalla et al, 2011; Perlis et al, 2005), (b) leading to more commercially favorable results (Batalla et al, 2011; Perlis et al, 2005; Williams et al, 2006), and (c) yet often not being disclosed (Anstey, 2018; Batalla et al, 2011) and in line with best practice dermatological standards (Anstey, 2018; British Association of Dermatologists, 2016b), studies were deemed to likely have a conflict of interest if explicit evidence suggested at least one (co)author (or co(author)’s affiliated employer or the study’s commercial funders) provided baldness interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Author bias may compromise the impartiality of research conclusions (2). The forward-thinking British Journal of Dermatology (BJD) addressed conflicts in a series of articles (3)(4)(5)(6). The BJD's editor stated the issue with crystal clarity: "Our judgement is influenced by conflict of interest" (7).…”
Section: An Evidence-based Evaluation Of Disclosurementioning
confidence: 99%
“…Two psychological mechanisms exist by which disclosure increases biased communications: strategic exaggeration (advice is more biased under the assumption that it will be discounted) and moral licensing (a sense of absolution from moral obligations to readers) (8-10). While disclosure attempts to discourage bias, empirical evidence suggests disclosure results in communications becoming more biased toward self-interests (2)(3)(4)(5)(6)(7)(8). A study that mimicked aspects of the patient-physician relationship involved estimators and advisors.…”
Section: An Evidence-based Evaluation Of Disclosurementioning
confidence: 99%